Un poco más y a lo mejor nos comprendemos luego. A methodological proposal for the study of lexical adverbs from historical morphosyntax and corpus-based analysis - Pérez Barajas, Alan Emmanuel (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
This paper presents a methodological proposal for the study of the adverb “luego” in Spanish, focusing on its grammaticalization process through a corpus-based analysis. This paper argues that “luego” has gone through several phases, from a locative adverb to become an argumentative and pragmadiscursive particle, which is evidenced in its trajectory of de-emanticization, subjectivization and discursivization. The research is supported by diachronic and synchronic data extracted from several corpora, such as CORDE, CREA and CORPES XXI, and complemented with examples from the Diccionario del español medieval (DEM). It is established that grammaticalization is a gradual and multifactorial process, where lexical items are transformed into grammatical ones, following the theories of Hopper and Traugott (2003) as well as Heine and Kuteva (2007) about grammaticalization. The methodology employed is mixed and is based on a sys tematic emptying of occurrences of “then”, classified according to semantic and functional criteria, as an immediate temporal adverb and discourse marker of consequence. We selected 400 occurrences of “luego” distributed proportionally among the corpora, which allows for a representative analysis of its use over time. The analysis reveals that in the CORDE corpus (13th-17th centuries), 91% of the occurrences of “luego” have a temporal value, while in CREA (20th-21st centuries) this percentage drops to 70%, with an increase in discursive uses reaching 20%. In the CORPES XXI corpus, discursive uses represent 32% of the occurrences, indicating an evolution towards more abstract functions. Finally, the author concludes that the study of the adverb “luego” is an exemplary case of grammaticalization in Spanish, highlighting the importance of combining quantitative and qualitative analyses to understand the processes of linguistic change. The research reinforces the idea that grammaticalization is a gradual and multifaceted process, where semantic, pragmatic and frequency factors converge.